PENGARUH BRAND POSITIONING DAN BRAND EQUITY TERHARAP KEPUTUSAN PEMBELIAN KENDARAAN - Memey Memey; Harlyn Lindon Siagian (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2019)
This study aims to examine and determine the effect of brand positioning and brand equity on the decisions of vehicle buyers. This research was conducted at PT. Arista Group with a sample of buyers or consumers who come to the company. The data processing method used in this study is descriptive statistical analysis, correlation coefficient test, coefficient of determination test, simple linear regression analysis, classic assumption test and hypothesis test (F test and t test) and multiple linear regression analysis. The results in this study indicate that multiple linear regression analysis is Buyer Decision = 5,559 + 0.720 BP + 0.113BE which means, the constant of 5,559 states that if there is no brand position and brand equity, the buyer's decision is 5,559. Partial hypothesis testing (Test t) brand positioning produces a coefficient obtained sig for the variable brand position is 0.000 then 0.000 <0.05 so Ha is accepted. Then t arithmetic is 6.403, then t count 0.05 so that H0 is accepted. Then you can see t count is 1,386, then t count> t table so there is in the area H0 accepted. So partially brand equity has a significant effect on buyer decisions. The conclusion is that there is a significant effect of brand positioning and brand equity on vehicle purchase decisions at PT. Arista Group.